Design and fabrication of agricultural sprayer / Muhammad Al-Hadi Rusli, Nur Kamarliah Kamardin and Ahmad Idzwan Yusuf - Rusli, Muhammad Al-Hadi; Kamardin, Nur Kamarliah; Yusuf, Ahmad Idzwan (School of Mechanical Engineering, 2023)
Agriculture is an essential industry, providing food for the world's population. However, the work involved in growing crops can be challenging, and farmers often face a variety of obstacles. One of the challenges farmers faces is using sprayers to protect their crops from pests and disease. Traditional sprayers can be heavy, cumbersome, and difficult to operate, making it challenging for farmers to spray their crops effectively. Body-mounted sprayers are a common type of sprayer used in agriculture. They require the farmer to carry the water container and pump the water by hand. This can be tiring and requires a significant amount of force, especially when covering large areas. Farmers may also need to carry additional supplies, such as pesticides and herbicides, which can add to the weight they must carry. To address these challenges, a new agricultural sprayer has been designed that offers several benefits to farmers. This sprayer is simple and easy to use, requiring only a small amount of force to operate. The water used for spraying is located on top of the project, eliminating the need for farmers to carry heavy water containers. The sprayer also pumps water automatically, eliminating the need for manual pumping. This new sprayer offers several advantages over traditional sprayers. It is lightweight, making it easier for farmers to carry and use. The automatic pumping system means that farmers can cover larger areas more efficiently, without tiring as quickly. This can help farmers save time and energy while ensuring that their crops are adequately protected. In conclusion, agriculture is a vital industry, and farmers face many challenges when growing crops. The new agricultural sprayer offers a simple and effective solution to one of these challenges. By making it easier for farmers to spray their crops, this new sprayer can help improve crop yields and reduce the physical strain on farmers